Combinational treatments of RNA interference and extracellular vesicles in the spinocerebellar ataxia - Ding, Yingying; Zhang, Yong; Liu, Xuehong (Frontiers in Molecular Neuroscience, 2022)
Spinocerebellar ataxia (SCA) is an autosomal dominant neurodegenerative disease (ND) with a high mortality rate. Symptomatic treatment is the only clinically adopted treatment. However, it has poor effect and serious complications. Traditional diagnostic methods [such as magnetic resonance imaging (MRI)] have drawbacks. Presently, the superiority of RNA interference (RNAi) and extracellular vesicles (EVs) in improving SCA has attracted extensive attention. Both can serve as the potential biomarkers for the diagnosing and monitoring disease progression. Herein, we analyzed the basis and prospect of therapies for SCA. Meanwhile, we elaborated the development and application of miRNAs, siRNAs, shRNAs, and EVs in the diagnosis and treatment of SCA. We propose the combination of RNAi and EVs to avoid the adverse factors of their respective treatment and maximize the benefits of treatment through the technology of EVs loaded with RNA. Obviously, the combinational therapy of RNAi and EVs may more accurately diagnose and cure SCA.